Complete replication of an animal virus and maintenance of expression vectors derived from it in Saccharomyces cerevisiae. - Price, B D (1996)
Here we describe the first instances to our knowledge of animal virus genome replication, and of de novo synthesis of infectious virions by a nonendogenous virus, in the yeast Saccharomyces cerevisiae, whose versatile genetics offers significant advantages for studying viral replication and virus-host interactions. Flock house virus (FHV) is the most extensively studied member of the Nodaviridae family of (+) strand RNA animal viruses. Transfection of yeast with FHV genomic RNA induced viral RNA replication, transcription, and assembly of infectious virions. Genome replication and virus synthesis were robust: all replicating FHV RNA species were readily detected in yeast by Northern blot analysis and yields of virions per cell were similar to those from Drosophila cells. We also describe in vivo expression and maintenance of a selectable yeast marker gene from an engineered FHV RNA derivative dependent on FHV-directed RNA replication. Use of these approaches with FHV and their possible extension to other viruses should facilitate identification and characterization of host factors required for genomic replication, gene expression, and virion assembly.